Telaah Nilai-Nilai Pribadi Konselor dalam Buku La Tahzan Karya ‘Aidh Al-Qarni - Fahma Islami (Irsyad : Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2020)
ABSTRACT The purpose of this study is to determine the structure and categorization of motivational messages. Not only that, this research also makes the implementation or use of messages as a material for Islamic Counseling Guidance. The researcher raises a framework of thought using the perspective of Religious Guidance and discourse analysis for the motivational message itself. This research method uses descriptive analysis of van Dijk's model of discourse analysis which states that there are three dimensions of text, consisting of: 1) text, 2) social cognition, and 3) social context, these three dimensions are in 3 levels of structure, namely: 1) macro structure, 2) superstructure, and 3) micro structure. From this explanation, it can be stated that a review of the counselor's personal values ​​in La Tahzan's book can be used as one of the main supports for the success of the process of providing assistance to clients and can be relied on as one of the materials of Islamic Counseling Guidance. Because there is material in a counseling process that will strengthen answers to the root of the problem, answer the real needs of the client and help achieve the goals of the counseling process. Keywords: Counselor; Study; Values.